THE WRITING OF THE SHOAH IN HUNGARIAN LITERATURE AFTER 1989. THE CASE OF MIHÁLY KORNIS (APPLICATION) - Piotrowiak-Junkiert, Kinga (Porównania, 2014)
In the first part of the article the author presents a few crucial cultural and political events, which have an association with the situation of Jews after the breakthrough of 1989. The subject of the article is the story entitled Application by Mihály Kornis from his book You live at last (Végre élsz). The writer belongs to the active Jewish authors. They have created a new canon of Hungarian literature. Kornis, who was aware of the situation and condition of Jews and their history in Hungary, breaks specific stereotypes of typical writing about Shoah. As a result of the De-Tabooisation concept he successfully creates a unique and original testimony of Jews’ fate.